Reproductive Health Literacy in Adolescent in Indonesia: a Scoping Review - Zulfa Mazida; Shrimarti Rukmini Devy; Rachmah Indawati (Indonesian Health Issue, 2026)
ABSTRACT Background: In Indonesia, discussions about reproductive health among adolescents remain constrained by cultural taboos, limited parental communication, and unequal access to accurate information, especially between urban and rural areas. These barriers contribute to low levels of reproductive health literacy. Purpose: This scoping review aims to identify the determinants influencing reproductive health literacy among Indonesian adolescents. Methods: A systematic search was conducted in Scopus, PubMed, and ProQuest databases on January 28, 2026, using Boolean operators with key terms such as "Reproductive," "Health Literacy," "Adolescent," and "Indonesia." Inclusion criteria were English-language articles from 2021–2025 focusing on Indonesian adolescents’ reproductive health literacy. After screening, 7 eligible articles were reviewed and analyzed thematically. Result: Findings that access to multiple sources of information especially digital platforms significantly improves adolescents’ reproductive health literacy and reduces risky behaviors. The internet and mass media emerged as dominant sources, followed by schools, peers, and parents. Socioeconomic status, age, family involvement, and formal education also play critical roles. Adolescents aged 16–24 generally exhibit higher levels of understanding. Cultural taboos, however, often restrict formal and familial discourse on reproductive health, causing adolescents to rely on less formal, and sometimes unreliable, sources. Conclusion: Improving reproductive health literacy among Indonesian adolescents requires a multifaceted approach that combines digital resources, structured school-based education, open family communication, and equitable access to healthcare. These interventions are essential to overcome cultural barriers and promote informed decision-making among youth.